2014
DOI: 10.14737/journal.jahp/2014/2.3.38.39
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Escherichia Coli from Pigs and Cattle

Abstract: Escherichia coli a gram negative rod shaped bacteria has been shown to be normal inhabitant of the gastrointestinal tract of animals and man and most of them are harmless, but some of the serotypes of it are pathogenic and causes diarrhoea and extra intra-intestinal infections in human and animals. A study was done to find out the prevalence of Escherichia coli from pigs and cattle from organized and unorganized farm in Assam. A total of 260 faecal samples, comprising 110 from cattle and 150 from pigs were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
3
1
Order By: Relevance
“…The higher incidence of Staphylococcus aureus in milk samples of subclinical mastitis of goats was recorded in this survey was also demonstrated by above workers. Escherichia coli are known as the most common environmental contaminants because these are found as a normal flora in the intestine of almost all farm animals (Ansari et al, 2014;Begum et al, 2014). From above workers, Sarker and Samad (2011) reported the incidence of Escherichia coli as a second most in subclinical mastitis milk samples, however in the present study we observed the Bacillus subtilis as second most prevalent organism.…”
Section: Prevalence and Incidence Of Bacterial Species In Subclinicalcontrasting
confidence: 61%
“…The higher incidence of Staphylococcus aureus in milk samples of subclinical mastitis of goats was recorded in this survey was also demonstrated by above workers. Escherichia coli are known as the most common environmental contaminants because these are found as a normal flora in the intestine of almost all farm animals (Ansari et al, 2014;Begum et al, 2014). From above workers, Sarker and Samad (2011) reported the incidence of Escherichia coli as a second most in subclinical mastitis milk samples, however in the present study we observed the Bacillus subtilis as second most prevalent organism.…”
Section: Prevalence and Incidence Of Bacterial Species In Subclinicalcontrasting
confidence: 61%
“…Our results showed that 95% of the collected samples were positive E. coli. the result is agreed with the finding previously obtained by (Begum et al, 2014), where 88.5 % of fecal samples were positive E. coli. While a lower percentage was obtained by (Oporto et al, 2008)), where only 35.9% of the examined samples were positive for E. coli.…”
Section: Discussionsupporting
confidence: 93%
“…As E. coli is mostly found on farm animals, it has been recognized as the most common environmental contaminant [ 59 , 60 ]. Our findings are very close to that of Moroni et al .…”
Section: Resultsmentioning
confidence: 99%